2020
DOI: 10.1177/1747954120919720
|View full text |Cite
|
Sign up to set email alerts
|

Importance of perceived teammate support as a predictor of student-athletes’ positive emotions and subjective well-being

Abstract: Student-athletes may have high stress, and the level of their subjective well-being could be low due to the dual role of being a student and an athlete. In the field of sport psychology, social support has received focal attention to identifying its impact on individuals’ subjective well-being. However, there is a lack of research that focuses on teammate support and subjective well-being. Thus, this study examined how the perception of teammate support influences subjective well-being through positive emotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 67 publications
0
4
0
1
Order By: Relevance
“…Social support is multidimensional, consisting of four types (i.e., emotional, instrumental, informational, esteem; Burleson et al, 2002; Freeman, 2020) and has been shown to be beneficial to athletes in a number of ways. Research has found that social support from coaches, teammates, friends, family, and sport administrators are beneficial for college athlete mental health and well-being and decreases burnout (Cho et al, 2020; DeFreese & Smith, 2013, 2014; Gabana et al, 2017; Hagiwara et al, 2017) and social support from teammates, coaches, and athletic trainers has related to improved recovery, well-being, satisfaction, and resilience (e.g., Corbillon et al, 2008; Galli & Vealey, 2008; Judge et al, 2012; Lu & Hsu, 2013). Emerging research on support for athlete activism, while limited, has found that perception of support is an important aspect of athletes’ experience engaging in activism (Martin et al, 2022).…”
Section: Challenges For Athlete Activistsmentioning
confidence: 99%
“…Social support is multidimensional, consisting of four types (i.e., emotional, instrumental, informational, esteem; Burleson et al, 2002; Freeman, 2020) and has been shown to be beneficial to athletes in a number of ways. Research has found that social support from coaches, teammates, friends, family, and sport administrators are beneficial for college athlete mental health and well-being and decreases burnout (Cho et al, 2020; DeFreese & Smith, 2013, 2014; Gabana et al, 2017; Hagiwara et al, 2017) and social support from teammates, coaches, and athletic trainers has related to improved recovery, well-being, satisfaction, and resilience (e.g., Corbillon et al, 2008; Galli & Vealey, 2008; Judge et al, 2012; Lu & Hsu, 2013). Emerging research on support for athlete activism, while limited, has found that perception of support is an important aspect of athletes’ experience engaging in activism (Martin et al, 2022).…”
Section: Challenges For Athlete Activistsmentioning
confidence: 99%
“…The support is given by the spectators and teammates during the match also affects the athlete's achievement. Teammate support had a positive influence on subjective well-being through positive emotion [19]. It was proven that during the race, the voices of the spectators were very busy supporting and watching the athletes competing so that the participants thought that their spirit and motivation would also increase.…”
Section: Discussionmentioning
confidence: 99%
“…In the sport context, several studies have explicitly investigated social support, with a majority of those studies investigating collegiate athlete perceptions of general support. For example, multiple studies have demonstrated that high levels of perceived social support from teammates, coaches, athletics department staff, family, and friends have positive impacts on mental health and well-being as well as were related to lower levels of burnout (Cho et al, 2020;DeFreese & Smith, 2013Gabana et al, 2017;Hagiwara et al, 2017;Sullivan et al, 2020). Further, higher levels of perceived social support from strength and conditioning coaches, athletic trainers, coaches, and teammates were recognized by athletes as having a large impact on their recovery, value of rehabilitation, feelings of well-being, and overall satisfaction (Barefield & McCallister, 1997;Bone & Fry, 2006;Corbillon et al, 2008;Judge et al, 2012;Lu & Hsu, 2013).…”
Section: Social Supportmentioning
confidence: 99%